Mulch de hojas trituradas de ficus en el rendimiento de Coriandrum sativum L. Loreto - Del Aguila Tapullima, Saul Fernando (2024)
This research aimed to evaluate the effect of ficus leaf mulch on the vegetative characteristics and yield of Coriandrum sativum L., a regional variety of cilantro. A completely randomized experimental design with ten replications in uniform horticultural beds was employed. Variables measured included plant height, bundle diameter, number of plants per bundle, and total bundle weight. The results showed significant improvements in all vegetative characteristics with the use of ficus leaf mulch. The average plant height with partially shredded leaf mulch was 23.0 cm (p < 0.001), bundle diameter was 13.60 cm (p < 0.001), and total bundle weight numerically improved with partially shredded leaf mulch at 487.60 g (p > 0.05). These results indicate that ficus leaf mulch not only promotes better vegetative growth of cilantro but also enhances its yield numerically. In conclusion, the use of ficus leaf mulch can be an effective horticultural practice to optimize cilantro production, offering benefits in terms of both quality and quantity of the crop.